Formulation and Activity Testing of n-Hexane Fraction of Brotowali Leaves (Tinospora crispa L.) for a Diabetic Ulcer Treatment - Kelly Tania; Novitaria Br Sembiring; Vera Estefania Kaban (Journal of Community Health Provision, 2026)
Diabetes mellitus is one of many degenerative illness with topmost number of cases in the world. One of the complications often created by diabetes mellitus is diabetic ulcer, which is susceptible to bacterial infection, obe of which is Staphylococcus aureus. This research wish to formulate an n-hexane fraction cream preparation from brotowali leaves (Tinospora crispa L.) and evaluate its antibacterial activity. Brotowali leaves were ectracted using 96% ethanol and the maceration method, then fractionates using n-hekxane. Then, antibacterial tests were implemented on the n-Hexane fraction using the disc method and formulates into a cream preparation with concentrations of 12,5%, 25% and 50%. The evaluation of the preparation was implemented by testing its spreadability, pH, homogeneity and organoleptic properties. Derived from the outcome of the study, it was shown that the n-Hexane fraction and Brotowali leaf cream formulation had inhibitory activity against Staphylococcus aureus, with the largest inhibition zone at a concentration of 50%. The n-Hexane fraction Brotowali leaf cream has the potential to be developed as a topical formulation for diabetic ulcers.